The relationship between students' learning approaches and their academic performance at UiTM Sarawak Samarahan Campus / Senian Malie [et.al.] - Malie, Senian; Haji Akir, Hajah Oriah; Daud, Mohd. Ghazali; Abang Awit, Abang Ahmad Ridzuan (2004)
he understanding of the students learning approaches, motives, and strategies is essential whether they are surface, deep, or achieving processors. The determination of how these approaches, motives, and strategies affect their academic performance is also of prime importance to academics and faculties. The research examines the association between the students learning approaches, motives, and strategies and their academic performance at UiTMCSKS. A total of 257 students participated in the study representing ten (10) diploma programs and three (3) undergraduate programs. The students were tested using a 42-scale item "Studying Process Questionnaires (SPQ)" adopted from Biggs (1987), and General Information Questionnaires (GIQ) designed by the authors. A separate of questionnaires were also distributed to all heads of programs in the study to investigate the expert views on whether there is any particular intervention programs in place for these students.